Building Better Communication in Tourism: How Cultural Competence and Language Skills Shape Service Performance - Rachim, Amanda Rizka; Salam, Dicky Arsyul (Journal of Tourism Sustainability, 2025)
In today's globalized tourism sector, frontline employees are increasingly expected to navigate intercultural interactions with Competence and agility. This study develops and empirically tests a structural model linking intercultural Competence, foreign language proficiency, organizational support, and international experience to communication self-efficacy, influencing strategic communication behaviors and enhancing communicative performance. Drawing on social cognitive theory, the model conceptualizes communication self-efficacy as a psychological bridge between underlying competencies and behavioral outcomes. Data were collected from 256 tourism professionals using a structured questionnaire and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that communication strategies significantly predict communicative performance and that communication self-efficacy strongly predicts strategic communication use. Foreign language proficiency, intercultural Competence, and organizational support each significantly enhanced self-efficacy, while international experience showed only a marginal effect. The findings advance theoretical understanding by positioning self-efficacy as a behavioral enabler that converts potential into performance. Practically, the study underscores the importance of integrated training models that go beyond technical knowledge to build confidence, strategic awareness, and organizational support. For tourism organizations aiming to deliver culturally responsive service, the results highlight the need to invest in skill development and empowering employees to act confidently in culturally complex settings.